No ureteral catheter mini percutaneous nephrolithotomy (NUC-mPCNL) achieves enhanced recovery after surgery (ERAS) - Xuwen Li; Zhongyu Tan; Yue Yu; Xiaochen Zhou; Haibo Xi; Wei Liu (Scientific Reports)
Abstract Conventional mini percutaneous nephrolithotomy (mPCNL) typically necessitates the pre-operative placement of ureteral catheters. With the development of enhanced recovery after surgery (ERAS), we introduce a novel approach: no ureteral catheter mini percutaneous nephrolithotomy (NUC-mPCNL). To evaluate the efficacy and safety of this innovative procedure compared to mPCNL, we compared the total operative time, stone clearance rate (SCR), stone-free rate (SFR), and complications among patients undergoing either modality from January to September 2021. Our findings revealed a statistically significant reduction in the mean total operative time for the NUC-mPCNL group (42.6 ± 2.4 vs. 60.2 ± 3.4 min, p < 0.001). The SCR, SFR and CSFR were comparable between two groups (98.5% vs. 97.8%, 84.3% vs. 76.0%, 64.7% vs. 60.0%, p = 0.337, 0.295, 0.625). WBC rise, hemoglobin drop and neutrophil percentage rise were similar in both groups. The overall complication rate in the NUC-mPCNL group was lower; however, the difference was not statistically significant (Clavien I, II and III; 11 vs. 13, 1 vs. 2 and 1 vs. 1). Consequently, we conclude that NUC-mPCNL effectively shortens the operative time and holds potential for expedited postoperative recovery.